Correlation of Preoperative Renal Insufficiency With Mortality and Morbidity After Aortic Valve Replacement: A Propensity Score Matching Analysis. Issue 9 (March 2016) - Lin, Chun-Yu; Tsai, Feng-Chun; Chen, Yung-Chang; Lee, Hsiu-An; Chen, Shao-Wei; Liu, Kuo-Sheng; Lin, Pyng-Jing
Abstract : Abstract: Preoperative end-stage renal disease carries a high mortality and morbidity risk after aortic valve replacement (AVR), but the effect of renal insufficiency remains to be clarified. Through propensity score analysis, we compared the preoperative demographics, perioperative profiles, and outcomes between patients with and without renal insufficiency. From August 2005 to November 2014, 770 adult patients underwent AVR in a single institution. Patients were classified according to their estimated glomerular infiltration rate (eGFR) as renal insufficiency (eGFR: 30–89 mL/min/1.73 m 2 ) or normal (eGFR, ≥90 mL/min/1.73 m 2 ). Propensity scoring was performed with a 1:1 ratio, resulting in a matched cohort of 88 patients per group. Demographics, comorbidities, and surgical procedures were well balanced between the 2 groups, except for diabetes mellitus and eGFR. Patients with renal insufficiency had higher in-hospital mortality (19.3% versus 3.4%, P < 0.001), a greater need for postoperative hemodialysis (14.8% versus 3.1%, P = 0.009), and prolonged intubation times (>72 hour; 25% versus 9.1%, P = .008), intensive care unit stays (8.9 ± 9.9 versus 4.9 ± 7.5 days, P = .046), and hospital stays (35.3 ± 31.7 versus 24.1 ± 20.3 days, P = .008), compared with those with normal renal function. Multivariate analysis confirmed that preoperative renal insufficiency was an in-hospital mortality predictor (odds ratio, 2.33; 95% confidence interval, 1.343–4.043; P = .003), as were prolonged cardiopulmonary bypass time, intraaortic balloon pump support, and postoperative hemodialysis. The 1-year survival significantly differed between the 2 groups including (normal 87.5% versus renal insufficiency 67.9%, P < .001) or excluding in-hospital mortality (normal 90.7% versus renal insufficiency 82.1%, P = .05). Patients with preoperative renal insufficiency who underwent AVR had higher in-hospital mortality rates and increased morbidities, especially those associated with hemodynamic instabilities requiring intraaortic balloon pump support or hemodialysis. Earlier surgical intervention for severe aortic valve disease should be considered in patients who show deteriorating renal function during follow-up.